Peran Keluarga Dalam Membentuk Karakter Anak Usia 6-12 Tahun di Desa Pagar Kecamatan Ulu Talo Kabupaten Seluma Provinsi Bengkulu - Dwi Permata Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The aims of this study were 1) to determine the role of the family in shaping the character of children aged 6-12 years in Pagar village, Ulu Talo District, Seluma Regency, Bengkulu Province, 2) to describe the supporting and inhibiting factors of the role of the family in shaping the character of children aged 6-12 years in Pagar Village, Ulu Talo District, Seluma Regency, Bengkulu Province. This type of research is a qualitative research with a descriptive approach. Research informants with primary data sources were 5 people as parents and secondary data sources were 2 representatives of uncles and aunts using the